2013
DOI: 10.1155/2013/472432
|View full text |Cite
|
Sign up to set email alerts
|

Roles for PI3K/AKT/PTEN Pathway in Cell Signaling of Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common form of liver pathologies and is associated with obesity and the metabolic syndrome, which represents a range of fatty liver diseases associated with an increased risk of type 2 diabetes. Molecular mechanisms underlying how to make transition from simple fatty liver to nonalcoholic steatohepatitis (NASH) are not well understood. However, accumulating evidence indicates that deregulation of the phosphatidylinositol 3-kinase (PI3K)/AKT pathway in hepato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
98
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(102 citation statements)
references
References 65 publications
3
98
1
Order By: Relevance
“…PTEN is among the proteins modified by TGFb1 and is a biological antagonist of PI 3 K signaling. Matsuda et al (2013) clarified the antagonistic relationship between PTEN and AKT and stated that PTEN has dual lipid and tyrosine-specific phosphatase activities that, if not physiologically regulated, could fundamentally alter cell behavior. Lan et al (2012) found that tubule PTEN was suppressed when TGFb1 signaling after AKI was persistently elevated and investigated its role in tubule repair.…”
Section: Discussionmentioning
confidence: 99%
“…PTEN is among the proteins modified by TGFb1 and is a biological antagonist of PI 3 K signaling. Matsuda et al (2013) clarified the antagonistic relationship between PTEN and AKT and stated that PTEN has dual lipid and tyrosine-specific phosphatase activities that, if not physiologically regulated, could fundamentally alter cell behavior. Lan et al (2012) found that tubule PTEN was suppressed when TGFb1 signaling after AKI was persistently elevated and investigated its role in tubule repair.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is consistent with a loss of activation of the AKT pathway, which has been identified as a key pathway for metabolism, cell growth, and cell survival. 36 Nevertheless, the PI3K/AKT pathways have been discussed to be the essential link between oxidative stress and inflammation in NASH. 36 Thus it is rather speculative if loss of AKT activation in AL mice on WD might be ascribed to the late phase of NAFLD with beginning carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The JAK2/STAT and the PI 3-kinase pathways regulate liver injury and regeneration [37], [38]. Thus, we hypothesized that hepatic SH2B1 may protect against liver injury as well as mediate growth hormone stimulation of somatic growth.…”
Section: Discussionmentioning
confidence: 99%